La documentación informativa en el nuevo espacio europeo de educación superior: Reflexiones desde la didáctica - Bas Martín, Nicolás (Revista General de Información y Documentación, 2007)
At this point of the process of European convergence, it is necessary to make an appeal to the university community so that it becomes aware of the changes that the European Higher Education area will mean. Not in vain, this process towards which we are irreversibly going means a deep revision of the prevailing pedagogical methods. In this case, we will try to apply some of these new principles to the subject of Informative Documentation, which needs to take into account an important methodological revision.